Sudden change of spall strength induced by shock defects based on atomistic simulation of single crystal aluminum. (15th March 2022) - Jiang, Dong-Dong; Shao, Jian-Li; Wu, Bao; Wang, Pei; He, An-Min
Abstract: This Letter interprets the detailed mechanism about the discontinuous variation in spall strength associated with shock-induced microstructure. It is known that elastic deformation, dislocation and stacking fault, as well as shock structural transition will appear in turn with the increase of shock intensity. Our molecular dynamics simulations of single-crystal aluminum reveal that the spall damage shows an evident dependence on the shock-induced microstructure. The nanovoids nucleate homogeneously in the region of elastic deformation or phase transition, resulting in higher spall strength. However, the nanovoids nucleate heterogeneously in the region of dislocation and stacking faults, which leads to a sudden decrease in spall strength. Different nucleation modes have a significant effect on the temperature response of spall strength. Under the condition of heterogeneous nucleation, the spall strength shows different temperature dependence and does not change inversely with temperature. Graphical abstract: Image, graphical abstract